Guyana : Poverty Reduction Strategy Paper Progress Report 2005. (IMF Staff Country Reports; Country Report, 2006)
Despite the continued vulnerability of the economy to exogenous shocks, the inadequacy of infrastructure, and the weakness of existing institutional capacity, there has been considerable progress in actions and reforms initiated by the government within the framework of the poverty reduction strategy. However, additional resources will have to be mobilized for Guyana to continue to improve its productive capacity, and to improve and maintain its infrastructure. The government has implemented an ambitious legislative and regulatory reform agenda to advance its support for economic growth.